A Novel Circuit Configuration for the Integration of Modular Multilevel Converter With Large-Scale Grid-Connected PV Systems - Elsanabary A.; Mekhilef S.; Seyedmahmoudian M.; Stojcevski A. (Institute of Electrical and Electronics Engineers Inc., 2025)
This article discusses the potential of using modular multilevel converters (MMC)s in large-scale photovoltaic (PV) systems. A novel modular circuit configuration for the integration of the PV system into the grid using MMC is proposed. The proposed circuit is modular, scalable, and has excellent performance during extreme PV shading conditions. Unlike other PV-MMC circuits, this circuit configuration eliminates the power unbalance between the arms of the converter. This feature enables the converter to deal only with the power unbalance occurring between the phases which eases the control process and ensures a wide range of power balancing of the MMC. A control strategy is adopted to provide a balanced operation of the converter under different conditions. It eliminates the power unbalance between the MMC phases by only injecting the dc circulating current component while the ac component is excluded which reduces the internal losses and increases the stability of the converter. The proposed circuit configuration and the control strategy are tested using the RT box Hardware-in-the-Loop technology. The corresponding analysis and results are provided to demonstrate the effectiveness and the excellent dynamic performance of the proposed system during various PV power generation conditions. ? 1986-2012 IEEE.